Potential of Dayak Onion (Eleutherine palmifolia) Extract and Powder as Natural Corrosion Inhibitors for SS400 Steel in NaCl Environment - Maftuhatun Khoiriyah; Paulus Hengky Abram; Vanny Maria Agustina Tiwow; Sitti Rahmawati (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Corrosion is a metal degradation process or a decrease in metal quality due to electrochemical reactions with its environment. This study aims to examine the potential of Dayak Onion (Eleutherine palmifolia (L.) Merr.) Bulb Extract and Powder as natural corrosion inhibitors on SS400 steel in a sodium chloride (NaCl) environment. The methods used include qualitative analysis of tannin compounds, determination of corrosion rate using the weight loss method, inhibition efficiency, determination of reaction order, and Scanning Electron Microscopy (SEM) testing to analyze surface morphology. The results showed that the lowest corrosion rate and highest inhibition efficiency were achieved after a 12-day immersion with the addition of 9 mL of extract, reaching 0.0014 mg/m² and an inhibition efficiency of 99.968%. Meanwhile, the powder showed the lowest corrosion rate and highest inhibition efficiency after a 12-day immersion with the addition of 9 grams, reaching 0.0008 mg/m² and an inhibition efficiency of 99.426%. Analysis showed that the corrosion rate followed a first-order pattern for both inhibitors, with the lowest corrosion rate constant of 0.000008 mg/day using 9 mL of concentrated extract and 9 grams of powder. These data indicate that both forms of inhibitor from Dayak onion bulbs can significantly inhibit the corrosion rate of SS400 steel, which has the potential for further application in the field of material protection.